Proactive business intelligence to give best customer experience to valued social networks in telecoms - Khan, Nusratullah; Shah, Asadullah; Khan, Shoab Ahmad; Anjum, Ali Raza (Springer, 2018)
To compete, cellular network operators must be very responsive to their customer needs. One effective approach that could make a business more productive is anticipatory decisions while considering customer’s problem. Communication Service Providers must have greater insights into their own Call Details Record data in order to gauge and tune up the company’s performance. CSPs must promptly react to ever changing competitive environment by providing quick and personalized services. However, reacting quickly to changing customer expectations is not a simple task. In this paper, a method has been proposed in order to tackle this challenging problem. Proposed solution is using CDR data as the primary data source to detect valued social networks and monitored the QOS provided to the identified valued social network. Calls of valued customers will be prioritized by inserting priority tag in MSC. The final step of proposed technique deduces a proactive approach in order to retain the high revenue generating customers.